Policy Stability in Climate Governance: The case of the United Kingdom. (15th August 2017) - Rietig, Katharina; Laing, Timothy
Abstract: 'Super‐wicked' problems such as climate change require ambitious policies within stable policy frameworks. Key for policy stability is to disincentivise future reversals to carbon‐intensive lifestyles resulting in unstoppable climate change. It requires lock‐in to a low‐carbon development trajectory, requires increasing popular support, and needs to be self‐reinforcing, with reversal costs rising over time as benefits increase. In parliamentary political systems (e.g. the UK), policies emerge more easily but are more difficult to maintain given that shifting political majorities can result in policy U‐turns, resulting in uncertainties for investment in low‐carbon transitions. We examine what factors determine policy stability in UK climate change policy that aims to reduce CO2 emissions by 85–90 per cent by 2050. Policy stability depends on favourable public opinion and the political system. In the case of parliamentary democracies the extent to which policy is embedded into a multilevel governance institutional framework and political cross‐party consensus is particularly important for stability. Copyright © 2017 John Wiley & Sons, Ltd and ERP Environment